Risk Factors for Lymph Node Metastasis in Undifferentiated-Type Gastric Carcinoma - Myeong-Cherl Kook (Korean Society of Gastrointestinal Endoscopy, 2019)
Undifferentiated-type carcinoma has a high incidence of lymph node metastasis. The independent risk factors for lymph node metastasis in undifferentiated-type carcinoma are invasion depth, tumor size, lymphovascular invasion, and presence of ulcer. In the cases that meet the curative resection criteria, no lymph node metastasis was observed in the Japanese studies, but some metastases were observed in Korean studies. After performing curative endoscopic submucosal dissection, the survival rate is similar to that of gastrectomy. The discrepancy between endoscopy and pathology is high in undifferentiated-type carcinoma. The tumor size in endoscopy is a significant risk factor for non-curative resection, and when the tumor size is small, the non-curative resection rate is significantly reduced. Lymphovascular invasion can be assessed in pathologic examination and D2-40 stain is helpful. The presence of ulcer should be determined by pathology, but ulcer's omission in pathology report makes the analysis difficult. Undifferentiatedtype carcinomas with differentiated-type components show higher lymph node metastasis rate than that of pure undifferentiatedtype carcinomas. The lymph node metastasis rate of signet ring cell type is lower than that of other undifferentiated-type carcinomas and is similar to differentiated-type carcinomas. The application of these additional histologic findings may improve the indication of endoscopic submucosal dissection.